DEVELOPMENT AND IN VIVO EVALUATION OF MUCOADHESIVE MICROSPHERES USING PIRENZEPINE - P, Kanteepan; Dvrn, Bhikshapathi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The current investigation objective was to fabricate gastroretentive mucoadhesive microspheres of pirenzepine and to investigate the pharmacokinetic parameters of optimized formulation in comparison with a marketed product. Methods: Pirenzepine mucoadhesive microspheres prepared using ionotropic gelation technique. Evaluation parameters and characterization such as Fourier transform infrared (FTIR) and scanning electron microscopy were performed. In vivo bioavailability studies were conducted in rabbits. The technique used was found to be handling easy, inexpensive, and reproducible process. Results: Among the total 14 formulations, M13 formulation was optimized and showed free flowing with good packability. FTIR studies investigated incompatibility were not observed between drug and excipients. The optimized formulation (M13) showed best cumulative percentage drug release of pirenzepine up to 99.07±0.17% within 12 h whereas marketed product displayed the drug release of 95.23±0.21% within 1 h. The release mechanism from microspheres followed the zero-order and Korsmeyer–Peppas model (R2=0.951 and 0.994), respectively. Optimized formulation (M13) was stable at 40°C±2°C/75% RH±5% RH for 6 months. Form in vivo studies, the optimized formulation bioavailability was much higher than the marketed product. Conclusion: Microspheres would be a promising drug delivery system could play a potentially significant role in pharmaceutical drug delivery in a controlled manner for an extended period of time for effective management of gastritis.